INTERNET BASED DATA AS A POWERFUL TOOL FOR TRACKING INFECTIOUS DISEASE DYNAMICS - Tatina T. Todorova; Gabriela S. Tsankova; Neli M. Ermenlieva (Peytchinski Publishing, 2021)
Purpose: Digital epidemiology (using Internet data as an epidemiological tool) is one of the most concurrent and novel approaches in the field of infectious disease tracking. We aimed to see if the disease-related information seeking via one of the most popular search engine (Google) correlates with the real varicella epidemiology in Bulgaria. Material/Methods: We compared the relative search index obtained by Google Trends with a keyword 'varicella' and the real incidence data for 2016-2018 in Bulgaria. Correlation analysis and t-test were used to see for association and difference in the means. Additionally, we summarized what type of information people find when searching for 'varicella'. Results: Dynamics of Google Trends with search term 'varicella' followed almost exactly the real dynamics of reported varicella cases in Bulgaria (Pearson's correlation coefficient of 0.85). The seasonality and the regional spread of varicella infection were also confirmed by the digital epidemiology (Pearson's correlation coefficient between the search index and the monthly cases was 0.93 and between the search index and the individual district incidence was 0.35). The majority of the information found by people during the seasonal varicella outbreaks was scientifically relevant and correct. Conclusions: Digital data received by non-epidemiological methods could be successfully used to study varicella dynamics, as high correlation exists between the data collected via the traditional methods and via the new, digital methodology.